Performance Comparison and Lysine Requirements of Seven Commercial Brown Egg Layer Strains During Phase One - Gunawardana, P.; Roland, D.A.; Sr.,; Bryant, M.M. (International Journal of Poultry Science, 2008)
This study was a 3 × 7 factorial arrangement of 3 lysine levels (0.917, 0.828 and 0.747) and seven commercial brown egg layer strains. The objective of this experiment was to determine the effect of increasing dietary lysine on performance, egg composition, egg solids, egg quality and profits in seven commercial brown egg layer strains and to determine the lysine requirement during phase one (from 21-36wk of age). This experiment lasted 16 weeks. Seven strains of hens (n = 240 of each strain) at 21 week of age were randomly divided into 21 treatments (8 replicates of 10 birds/treatment). The results showed that there were no interactions between lysine and strain on any parameter. Lysine had significant effects on egg weight, egg mass, feed conversion, percent albumen solids, yolk color, shell color, albumen weight, egg shell and albumen components. There were significant strain effects on egg production, feed consumption, egg weight, egg mass, feed conversion, specific gravity, yolk weight, shell color, shell, albumen and yolk components, yolk, albumen and whole egg solids. Strain 1 had the best overall performance. All strains peaked in production over 94% and were laying 94-96% at 36 weeks of age. Average egg weight (21-36wk) was 60.3g, varying from 59.0-62.8g between strains. Average feed intake was 112.3g/hen/day varying from 109.6-116.7g/hen/day between strains. Average egg weight of hens fed diets containing the highest lysine level was 2.04g heavier than the hens fed the diets containing the lowest lysine level. Increasing dietary lysine from 0.747-0.917% significantly improved feed conversion from 2.20-2.06g feed/g egg and increased egg mass from 51.8-54.32g/hen/day. Average lysine intake of hens fed 0.917% level was 1023mg/hen/day varying from 1005-1070mg/hen/day between strains. Because egg prices and ingredient prices often change, there can be no fixed dietary lysine level for optimal profits.